Job Loss and Retirement Behavior of Older Men - Sewin Chan; Ann Huff Stevens (Rutgers University, Department of Economics, 1999)
This paper uses data from the Health and Retirement Study to examine the employment and retirement behavior of men aged fifty and above who have experienced an involuntary job loss. Hazard models for returning to work and for exiting post-displacement employment are estimated and used to examine work patterns for ten years following a job loss. The findings show that a job loss results in large and lasting effects on future employment probabilities, and that these effects vary with the age of the worker. Displaced workers in their fifties are estimated to have a three in four chance of returning to work within two years after a job loss, whereas for a 62-year-old job loser, the probability is less than a third. Once re-employed, workers of all ages initially face significantly higher probabilities of exiting the workforce than do workers who have not experienced a recent job loss; however, this effect gradually reverses over time. The net outcome of these entry and exit rates is a substantial gap between the employment rates of men who have and have not lost jobs, that lasts at least seven years. The employment rates of men who lose jobs in their fifties eventually converge with those of non-displaced workers of the same age, as the latter retire at a rapid rate during their sixties.
Keywords: J26; J64; 330; aging; displacement; employment; retirement